Effectiveness of low dose thyroxine in patients with subclinical hypothyroidism and migraine; systematic review and meta-analysis - Alia Alokley; Maryam N. ALNasser; Razan Anwar Alabdulqader; Faisal Abdulhamid Aljohni; Duaa Hussain Alqadhib; Rose Khalid Aljuaid; Montather Akeel Alshik Ali; Shahad Shadi Hanbazazah; Abdullah Almaqhawi (BMC Neurology)
Abstract Background Subclinical hypothyroidism (SCH) is defined by elevated thyroid-stimulating hormone (TSH) levels alongside normal free thyroxine (T4) and triiodothyronine (T3) levels. Emerging evidence suggests a link between SCH and migraine disorders, including both episodic and chronic migraine. Given this association, researchers have explored whether correcting mild thyroid dysfunction with low-dose levothyroxine could alleviate migraine symptoms in affected individuals. This study investigates the potential efficacy of low-dose thyroid replacement therapy in reducing migraine frequency and severity among patients with comorbid SCH and migraine. Methods A search was conducted on Cochrane Central, Medline, Embase, Web of Science Core Collection, and Scopus to identify randomized clinical trials (RCTs), case-control studies, and cohort research studies evaluating the use of low-dose thyroxine in patients with subclinical hypothyroidism (SCH). Results This review analyzed four studies, two of which qualified for meta-analysis. The findings suggest a potential association between (SCH) and migraine. Notably, levothyroxine treatment in hypothyroid patients appeared to correlate with reduced migraine frequency and headache severity. However, while the meta-analysis showed a trend toward migraine reduction with thyroxine therapy, the results did not reach statistical significance - likely due to the limited study sample included in the analysis. Conclusion The study highlights the importance of thyroid screening in migraine management, due to the link between hypothyroidism and migraines. It recommends routine thyroid function assessments for migraine patients and suggests personalized treatment approaches. Early intervention can minimize migraine episodes and improve quality of life. Adherence to low dose levothyroxine regimens can reduce migraine frequency. Further research is required to elucidate the underlying mechanisms, optimize treatment protocols, and explore potential comorbidities.